210Po and 210Pb distributions during a phytoplankton bloom in the North Atlantic: Implications for POC export. (October 2020) - Horowitz, Evan J.; Cochran, J. Kirk; Bacon, Michael P.; Hirschberg, David J.
Abstract: During the North Atlantic Bloom Experiment (NABE) of the Joint Global Ocean Flux Study (JGOFS), water column sampling for particulate and dissolved 210 Po and 210 Pb was performed four times (26 April and 4, 20, 30 May 1989) during a month-long Lagrangian time-series occupation of the NABE site, as well as one-time samplings at stations during transit to and from the site. There are few prior studies documenting short-term changes in 210 Po and 210 Pb profiles over the course of a phytoplankton bloom, and we interpret the profiles in terms of the classical "steady-state" (SS) approach used in most studies, as well as by using a non-steady state approach suggested by the temporal evolution of the profiles. Changes in 210 Po profiles during a bloom are expectable as this radionuclide is scavenged and exported. During NABE, 210 Pb profiles also displayed non-steady state, with significant increases in upper water column inventory occurring midway through the experiment. Export of 210 Po from the upper 150 m using the classic "steady-state" model shows increases from 0.5 ± 8.5 dpm m −2 d −1 to 68.2 ± 4.2 dpm m −2 d −1 over the one-month occupation. Application of a non-steady state model, including changes in both 210 Pb and 210 Po profiles, gives higher 210 Po export fluxes. Detailed depth profiles of particulate organic carbon (>0.8 μm) and particulate 210 Po (>0.4 μm) are available from the 20 and 30 May samplings and show maxima in POC/Po at 37 m. Applying the POC/ 210 Po ratios at 150 m to the "steady state" 210 Po fluxes yields POC export from the upper 150 m of 8.2 ± 1.5 mmol C m − 2 d −1 on 20 May and 6.0 ± 1.6 mmol C m −2 d −1 on 30 May. The non-steady state model applied to the interval 20 to 30 May yields POC export of 24.3 mmol C m −2 d −1 . The non-steady state (NSS) 210 Po-derived POC fluxes are comparable to, but somewhat less than, those estimated previously from 234 Th/ 238 U disequilibrium for the same time interval (37.3 and 45.0 mmol m −2 d −1, depending on the POC/Th ratio used). In comparison, POC fluxes measured with a floating sediment trap deployed at 150 m from 20 to 30 May were 11.6 mmol m −2 d −1 . These results suggest that non-steady state Po-derived POC fluxes during the NABE agree well with those derived from 234 Th/ 238 U disequilibrium and agree with sediment trap fluxes within a factor of 2. However, unlike the 234 Th-POC flux proxy, non-steady stage changes in profiles of 210 Pb, the precursor of 210 Po, must be considered. Highlights: Changes in the distributions of 210 Po and 210 Pb in the North Atlantic Ocean (46°N, 20°W) over the course of a spring phytoplankton bloom. 210 Po and 210 Pb distributions reflect course of the bloom, with 210 Po deficits relative to 210 Pb increasing over time. Particle uptake of 210 Po in early bloom: deficits relative to 210 Pb as particles aggregate and sink as nutrients are depleted. 210 Po deficit (150 m) is converted to the sinking flux of particulate organic carbon (POC) using the POC/ 210 Po. Po-derived POC fluxes agree (factor of 2) with those determined independently using floating sediment traps and 234 Th/ 238 U.